Effectiveness of acupuncture on pregnancy success rates for women undergoing in vitro fertilization: A randomized controlled trial - Pinar Gursoy Guven; Yasemin Cayir; Bunyamin Borekci (Elsevier, 2020)
Objective: To investigate the effect of acupuncture on pregnancy success rates applied before and after embryo transfer (ET) among women undergoing in vitro fertilization (IVF). Materials and methods: In this randomized controlled trial, 72 infertile women undergoing IVF were randomized to acupuncture (AG; n = 36) and control group (CG; n = 36). Three sessions of acupuncture were applied to AG, the first was one week before ET, the second was 30 min before ET, and the third was 30 min after ET. CG received no acupuncture. The primary outcome was pregnancy success rate (Beta-HCG level, clinical pregnancy, ongoing pregnancy, live birth). Secondary outcome was anxiety level (STAI-1 state anxiety scale). Beta-HCG levels were assessed for conception 12 days after ET. Additionally, STAI-1 state anxiety scale was administered 30 min before and after ET to measure anxiety levels in both groups. Results: The mean age was 30.9 ± 3.7 years. Positive Beta HCG was detected in 63.9% (n = 23) of the AG and 33.3% (n = 12) of CG (p = 0.009). Clinical pregnancy, ongoing pregnancy, and live birth rates were higher in AG (p < 0.05). There was no difference between the groups concerning anxiety scores before ET (p > 0.05). The mean STAI-1 score was decreasing from 57.3 ± 9.8 to 28.8 ± 3.3 in AG, while it was decreasing from 57.0 ± 8.0 to 41,1 ± 6,8 in CG after ET (p < 0.000). Conclusions: It was observed that three sessions of acupuncture before and after ET significantly increased the pregnancy rates in women with unexplained infertility. It was also found that acupuncture significantly reduced anxiety levels that occurred before ET. Keywords: Acupuncture, Embryo transfer, Infertility, In vitro fertilization, Pregnancy